2021
DOI: 10.1016/s2214-109x(21)00292-8
|View full text |Cite
|
Sign up to set email alerts
|

Retraction—Family planning in COVID-19 times: access for all

Abstract: In this invited Comment, 1 significant portions of text were used verbatim from several other pieces of published work without proper attribution. Although the sources were cited, the verbatim text should have been indicated by quotation marks. I therefore wish to retract this Comment. I sincerely regret the lapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…Thirteen articles in journals with the highest impact factors (>10) were analyzed in more detail to determine the explanation for the retraction (Table 4). [6][7][8][9][10][11][12][13][14][15][16][17][18] The impact factor for these journals ranged from 10.6 to 168.9. The most frequent reason for retraction was either concerns about data validity (n = 3) or unreliable results (n = 3).…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen articles in journals with the highest impact factors (>10) were analyzed in more detail to determine the explanation for the retraction (Table 4). [6][7][8][9][10][11][12][13][14][15][16][17][18] The impact factor for these journals ranged from 10.6 to 168.9. The most frequent reason for retraction was either concerns about data validity (n = 3) or unreliable results (n = 3).…”
Section: Resultsmentioning
confidence: 99%
“…Limiting access to family planning information and services is one of the problems that accompanied with pandemic, COVID-19 has negatively affected health systems in worldwide, lockdown countries and people forced to staying at home, low of economic status, and inability to communicate with parents, friends, and health care providers all of this affected women sexual and reproductive health. [16][17][18][19][20] More than half of women are exposed to domestic violence due to pandemic of COVID-19; 51.1% are reported they exposed to domestic violence due to pandemic and husband's stay in home for long time, 51.7% reported increased domestic violence during pandemic, and 38.3% reported that their husband didn't care about her sexual feelings.…”
Section: Originalmentioning
confidence: 99%